THE ILLEGAL TRADING (RED MARKET) OF MEDICINAL PLANTS IN SOUTH AFRICAN RURAL AREAS: A SCOPING REVIEW - Witness Maluleke; Nyiko Faith Shibambu (CV. RADJA PUBLIKA, 2024)
The widespread of illegal trading (Red market) of medicinal plants has reached a concerning phase in South Africa rural areas. This prohibited practice involves a global black market for instant monetary gain, usually committed by illegal collections and sales of these plants, fuelling their scarcity. Therefore, the objective of this study was to explore the illegal trading of medicinal plants in South African rural areas. This qualitative scoping review was supported by the 2005 adapted version of the methodology framework by Arksey, Hilary & O’Malley, Lisa of 2005 to search for relevant studies from notable databases and internet sources, focusing on South African rural areas and other international countries, optionally. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) will be used for data analysis, supported by the inductive Thematic Content Analysis (TCA).The findings of this study present that the illegal trading of medicinal plants is on the rise in South African rural areas owing to the illegal trading, with the potential criminals reportedly less likely to face consequences of their ill actions and the greatest factor of their scarcity is attributed to this practice, with less efforts offered for greater adequate attention geared towards conservation and safeguarding of these vulnerable plants. It is concluded and recommended that the chain of events of illegal trading should be established closely looking at a period when this illegal action is committed, reported to the selected relevant stakeholders, such as the ‘African National Healers Association (ANHA), Department of Correctional Services (DCS), Department of Justice and Constitutional Development (DoJ & CD), PlantZAfrica, South African Local Government Association (SALGA), South African National Biodiversity Institute (SANBI), South African Police Service (SAPS), who are responsible for the investigation, prosecution, incarceration and rehabilitation of suspected and convicted criminals. Moreover, effective deterrents to this criminality should be further researched to broaden access to justice and strengthen prevention, combating and investigative initiatives by relevant stakeholders in the local government sphere, where towns and surrounding rural areas are going to be accountable for the protection and preservation of heritage.